Single-cell cloning and its approaches - Ammar, Amany E. S. (Frontiers in Cell and Developmental Biology, 2025)
Single-cell cloning (SCC) is a technique for the production of a pure clone from a single parental cell. SCC has become a fundamental process in biological research. It has many crucial applications, ranging from the production of therapeutic proteins to stem cell-based therapies. However, a main obstacle with SCC has been the difficulty in establishing and scaling single-cell derived clones. Various methods and tools have been developed to facilitate SCC. This review provides an overview of the most common techniques for SCC. The selection among these techniques is contingent upon several factors, including available resources, cell proliferation capacity, number of needed clones, and expertise.